Meaning, metaphor, and argument structure. - NISBET, TIM; De Wit, Astrid; Brisard, Frank (Journal of Linguistics, 2019)
This paper challenges what it calls the semantic determinist hypothesis (SDH) of argument licensing, according to which the syntactic realisation of a verb's arguments is a function of its semantic properties. Specifically, it takes issue with 'event schema' versions of the SDH applied to the English ditransitive alternation (give/send {Jesse the gun/the gun to Jesse}), which claim a systematic, syntactically predictive distinction between 'caused possession' and 'caused motion'. It is first shown that semantic and syntactic irregularities among the alternating verbs disconfirm such a mapping. More crucially, however, it is argued that 'non-prototypical' (metaphorical and idiomatic) usage (The news report gave Walt an idea, Walt's actions gave the lie to his promises, The discovery sent Jesse into a fury) is fatal to the SDH, since the hypothesis entails the existence of semantic constraints on argument realisation which these expressions violate. Based on an analysis of the semantically-related verbs give, send, and put, it is claimed that prototypical, metaphorical and idiomatic expressions of a verb can all be licensed straightforwardly, but only if theory maintains separate syntactic and semantic representation of arguments in lexical entries, observing the 'parallel architecture' of Jackendoff (1997, 2002), and only if argument tokens are licensed by the syntactic representation alone. A type of structure called a Lexical Argument Construction is proposed, which can describe all the relevant properties of verbs and verbal idioms.